Natural resources and environmental sustainability: COP26 targets from resources-based perspective - Peng, Li; Li, Yongchang; Raza, Syed Ali; Shahzadi, Irum [UNESP] (Elsevier, 2023)
In current era, the issue of environmental quality degradation is attracting scholars' and policymakers' attention. As a consequence of the COP26 target, both developed and emerging economies are struggling to attain the carbon neutrality target. Since the existing literature is rich for developed countries' environmental assessment. This research analyzes the nexus of natural resources and carbon (CO2) emissions. Unlike the prevailing studies, which cover only one or total natural resources, this research covers all the components of natural resources separately, which is a novel contribution in emerging economies. Besides, this study also considered the role of economic growth, urbanization, and renewable energy consumption on carbon emissions. The study's empirical results validate the existence of cointegration between the variables. Using non-parametric estimators, the study explored that each component of natural resources has a specific influence on CO2 emission. Where the impact of rents for coal, forest, and mineral are positive while negative for natural gas rents. On the other hand, the impact of oil rents is mixed with CO2 emissions, which are negative in lower quantiles and positive in the upper quantiles. In addition, the study found that economic growth is a significant driver of emission, whereas the increased emissions could be significantly reduced via renewable energy consumption and urbanization. This study suggests the increased production of renewables and efficient utilization of natural resources to attain the COP26 target.
Keywords: Carbon emissions; COP26; Economic growth; Emerging economies; Natural resources; Resource rents; Urbanization